Arte contemporânea na formação de professores [manuscrito]: um estudo com alunos da licenciatura em artes visuais da UFG - VALENÇA, Kelly Bianca Clifford (2009)
The way artifacts influence and are influenced by culture is a recurrent topic in the contemporary scene. Images, toys and art works integrate such ideological framework which impels behavior and contributes for an alienated consumption. To educate in a context in which images seduce and attract for consumption invading our daily life is one of the challenges of art teaching. Contemporary art has a potential to give voice to students subjectivity and to promote dialogical, critical and inclusive learning. This work investigates the way how six students, future teachers three women and three men attending the Visual Arts Teaching Program at the Visual Arts College of the Federal University of Goiás, understand and interrelate with contemporary art images as their teaching object. Inspired on my observations concerning the resistance to the use of these images in classrooms, this research constitutes a sample of collected data that builds a net of point of views that sometimes overcross, sometimes diverge, but, especially, reflect pedagogical, social and cultural issues naturalized in the understandings and conceptions of those future teachers. Developed through individual interviews and focal groups, this investigation is oriented by a qualitative methodological perspective which considers images, talks, silences, gestures and reactions as part of a critical and constructive analysis of narratives that dialogue with visual culture